Amount and spatial distribution of habitats influence occupancy and dispersal of frogs at multiple scales in agricultural landscape - Faggioni, Gabriel P.; Souza, Franco L.; Paranhos Filho, Antonio C.; Gamarra, Roberto M.; Prado, Cynthia P. A. [UNESP] (Wiley-Blackwell, 2020)
Agriculture changes the aquatic and terrestrial habitats used by animals, affecting their responses to matrix permeability. Here, we evaluated the impacts that resulted from the replacement of native vegetation with pastures on habitat occupancy, colonisation and local extinction of two Neotropical frogs with contrasting ecological strategies, Leptodactylus bufonius and L. chaquensis. We conducted fieldwork during two reproductive seasons in 50 temporary ponds in the Brazilian Chaco. We used site occupancy models in a multi-scale approach to identify landscape changes affecting population parameters and to determine the scale of interaction between species and the landscape. At local (10 m) and scales <= 400 m, increased pasture proportion limited the availability of bare soil required by males of L. bufonius to build mud chambers for reproduction and decreased proportion of shrublands affecting L. chaquensis occupancy. At larger spatial scales (>400 m), landscape modification limited dispersal of the smaller species L. bufonius. We found that the amount of habitat available is important in maintaining population parameters such as occupancy. However, our results highlight that the spatial distribution of habitats may also play an important role in the persistence and mobility of frogs in agricultural landscapes and that it is possible to identify a scale of effect in such anthropic landscapes. We recommend the consideration of reproductive and dispersal requirements of amphibian species, along with body size, as predictors of the spatial scale for management of populations in farmlands.
Keywords: Amphibia; Chaco; landscape ecology; population ecology; scale of effect